Design and performance of very low head water turbines using a surface vorticity model algorithm - Ridwan Arief Subekti; Budi Prawara; Anjar Susatyo; Ahmad Fudholi; Sastra Kusuma Wijaya; Arief Sudarmaji (Institute of Advanced Engineering and Science, 2022)
This study explores the numerical optimization of water turbine runner profile performance using a surface vorticity model algorithm. The turbine is designed on a laboratory scale and operates at a net head of 0.09 m, 400 rpm, and a water flow rate of 0.003 m3/s. The initial design of the turbine runner was optimized to minimize losses in the hydrofoil. The optimization algorithm is coded in MATLAB software to obtain the optimal stagger angle that will be used in the water turbine design. Furthermore, design validation was performed using computational fluid dynamics analysis ANSYS CFX to determine the water turbine performance. The settings used in ANSYS CFX include the reference pressure of 1 atm, turbulence model shear stress transport, and inlet boundary conditions using total pressure and static pressure outlet boundary conditions. The computational fluid dynamics analysis reveals that by optimizing the design, the efficiency of the water turbine increases by approximately 2.6%. The surface vorticity model algorithm can be applied to optimize the design of the water turbine runner.